Sudden unexpected death in epilepsy in patients treated with brain‐responsive neurostimulation. (16th January 2018) - Devinsky, Orrin; Friedman, Daniel; Duckrow, Robert B; Fountain, Nathan B; Gwinn, Ryder P; Leiphart, James W; Murro, Anthony M; Van Ness, Paul C
Summary: Objective: To study the incidence and clinical features of sudden unexpected death in epilepsy (SUDEP) in patients treated with direct brain‐responsive stimulation with the RNS System. Methods: All deaths in patients treated in clinical trials (N = 256) or following U.S. Food and Drug Administration (FDA) approval (N = 451) through May 5, 2016, were adjudicated for SUDEP. Results: There were 14 deaths among 707 patients (2208 postimplantation years), including 2 possible, 1 probable, and 4 definite SUDEP events. The rate of probable or definite SUDEP was 2.0/1000 (95% confidence interval [CI] 0.7‐5.2) over 2036 patient stimulation years and 2.3/1000 (95% CI 0.9‐5.4) over 2208 patient implant years. Stored electrocorticograms around the time of death were available for 4 patients with probable/definite SUDEP and revealed the following: frequent epileptiform activity ending abruptly (n = 2), no epileptiform activity or seizures (n = 1), and an electrographic and witnessed seizure with cessation of postictal electrocorticography (ECoG) activity associated with apnea and pulselessness (n = 1). Significance: The SUDEP rate of 2.0/1000 patient stimulation years among patients treated with the RNS System is favorable relative to treatment‐resistant epilepsy patients randomized to the placebo arm of add‐on drug studies or with seizures after resective surgery. Our findings support that treatments that reduce seizures reduce SUDEP risk and that not all SUDEPs follow seizures.